2016
DOI: 10.3758/s13421-016-0585-z
|View full text |Cite
|
Sign up to set email alerts
|

Preexisting semantic representation improves working memory performance in the visuospatial domain

Abstract: Working memory (WM) for spoken language improves when to-be-remembered items correspond to pre-existing representations in long-term memory. We investigated whether this effect generalizes to the visuospatial domain by administering a visual n-back WM task to deaf signers and hearing signers as well as hearing non-signers. There were four different kinds of stimuli: British Sign Language (BSL, familiar to the signers); Swedish Sign Language

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(42 citation statements)
references
References 49 publications
1
39
2
Order By: Relevance
“…Recent findings indicate that non-lexical manual gestures are more difficult to process than are lexical manual gestures both for signers and non-signers Rudner et al, 2016). These earlier findings relating to adults were here replicated for children.…”
Section: Gesture Type and A Surprising Effect Of Sign Language Experisupporting
confidence: 75%
See 1 more Smart Citation
“…Recent findings indicate that non-lexical manual gestures are more difficult to process than are lexical manual gestures both for signers and non-signers Rudner et al, 2016). These earlier findings relating to adults were here replicated for children.…”
Section: Gesture Type and A Surprising Effect Of Sign Language Experisupporting
confidence: 75%
“…The phonology of a sign language often carries semantic information (Thompson, Vinson, Woll, & Vigliocco, 2012), and some earlier studies indicate that semantic information, in addition to phonological, does not influence the processing efficiency of sign-based stimuli in deaf adults (e.g., Cardin et al, 2016;Rudner et al, 2016). This may explain why no difference in performance was found between familiar and unfamiliar signs for DHH signing children in the present study.…”
Section: Imitation Precision Of Familiar and Unfamiliar Signscontrasting
confidence: 37%
“…These authors suggested one reason for this finding might be that hearing signers are more likely to use English subvocal rehearsal than deaf signers, which could facilitate serial recall (see Hall and Bavelier, 2011). Rudner et al (2016) also suggest that hearing signers may make strategic use of their speech-based representations for mnemonic purposes. However, the pattern of findings from our study argues against this interpretation because we found an advantage for English over ASL for hearing bilinguals on the STM task.…”
Section: Discussionmentioning
confidence: 99%
“…When only matching phonological representations are available, a cohort of lexical candidates will be activated ( Marslen-Wilson, 1987 ) that is unconstrained by meaning, and language processing will probably be less efficient. When input bears reduced phonological information, phonological constraints will be fewer and processing will probably be even less efficient ( Rudner et al, 2016 ). These factors are likely to be of importance even in the developing language system ( Mann et al, 2010 ; Sundström et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in the present study, we predicted that Swedish DHH signing children would be better at imitating SSL signs with both semantic and phonological information than BSL signs with phonological information only, and better at imitating lexical signs (SSL and BSL) than non-signs with reduced phonological information. Because recent studies indicate that non-signs are more difficult to process than lexical signs, even for non-signers ( Cardin et al, 2016 ; Rudner et al, 2016 ), we predicted that both groups would be better at imitating lexicalized signs (both SSL and BSL) than non-signs.…”
Section: Introductionmentioning
confidence: 99%